2014
DOI: 10.1136/amiajnl-2013-002229
|View full text |Cite
|
Sign up to set email alerts
|

Electronic health record functionality needed to better support primary care

Abstract: Electronic health records (EHRs) must support primary care clinicians and patients, yet many clinicians remain dissatisfied with their system. This article presents a consensus statement about gaps in current EHR functionality and needed enhancements to support primary care. The Institute of Medicine primary care attributes were used to define needs and meaningful use (MU) objectives to define EHR functionality. Current objectives remain focused on disease rather than the whole person, ignoring factors such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 27 publications
1
64
0
2
Order By: Relevance
“…EHRs may provide a foundation for improving the delivery of primary care by enabling the collection, measurement, and reporting of patient outcomes and quality of care. [34][35][36] The ABP itself has recognized the critical role of health information systems in facilitating QI activities as part of MOC. 37 When e7…”
Section: Discussionmentioning
confidence: 99%
“…EHRs may provide a foundation for improving the delivery of primary care by enabling the collection, measurement, and reporting of patient outcomes and quality of care. [34][35][36] The ABP itself has recognized the critical role of health information systems in facilitating QI activities as part of MOC. 37 When e7…”
Section: Discussionmentioning
confidence: 99%
“…16,17 In response to concerns like these, a recently published primary care consensus statement concluded that many EHR systems need marked refinement to promote greater patient engagement. 18 One proposed solution to improve patient engagement and the flow of information while using EHRs during the clinical encounter is the use of medical scribes. While the roles of scribes can vary based on the nuances of a given clinical setting, in general scribes are personnel specifically hired to chart patient-clinician encounters in real time, from the beginning of the encounter to its end.…”
mentioning
confidence: 99%
“…Personal doctors must take action to ensure that health IT enhances rather than diminishes relationships and patient care. We can participate in the development of new EHR functionality that better supports personal doctoring and relationships, 16 insisting that this functionality be prioritized over the billing and transactional features that have dominated EHR design. Personal doctors can help to enable technology and data to inform our collaborations with patients, families, and communities.…”
Section: Strengthening Relationships Through Technologymentioning
confidence: 99%